2012
DOI: 10.1021/nn204166z
|View full text |Cite
|
Sign up to set email alerts
|

Concentrated Dispersions of Equilibrium Protein Nanoclusters That Reversibly Dissociate into Active Monomers

Abstract: Stabilizing proteins at high concentration is of broad interest in drug delivery, for treatment of cancer and many other diseases. Herein, we create highly concentrated antibody dispersions (up to 260 mg/mL) comprising dense equilibrium nanoclusters of protein (monoclonal antibody 1B7, polyclonal sheep immunoglobulin G, and bovine serum albumin) molecules which, upon dilution in vitro or administration in vivo, remain conformationally stable and biologically active. The extremely concentrated environment withi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
162
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 104 publications
(171 citation statements)
references
References 69 publications
6
162
1
Order By: Relevance
“…In the weak screening limit, this is relevant because the effective repulsion between two NPs from different SPs incorporates the many-body effects from constituent NPs in each SP. In the strong screening limit and with sufficiently big counterions (16) or with stabilizing polymers (27,29), the accumulation of the counterion layers (or adsorbed polymeric stabilizers) causes the increase in A inter ij as the SPs grow in size. Using the argument as above, we propose that the repulsion strength between the NPs in the same SP, A intra ij , also depends on the relative positions of the NPs to the SP center of mass.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…In the weak screening limit, this is relevant because the effective repulsion between two NPs from different SPs incorporates the many-body effects from constituent NPs in each SP. In the strong screening limit and with sufficiently big counterions (16) or with stabilizing polymers (27,29), the accumulation of the counterion layers (or adsorbed polymeric stabilizers) causes the increase in A inter ij as the SPs grow in size. Using the argument as above, we propose that the repulsion strength between the NPs in the same SP, A intra ij , also depends on the relative positions of the NPs to the SP center of mass.…”
Section: Methodsmentioning
confidence: 99%
“…Because van der Waals forces decay much faster than electrostatic forces and are less sensitive to screening effects (27), the total van der Waals attraction increases with the SP radius (26). Using the same renormalization rationale as above, we observe that the rate of change in e inter ij ∼ V…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Simulations show that model particles form clusters in crowded conditions (Figure 2A) [24]. Cluster formation is observed quite commonly in colloidal systems [25], and the concentration of protein in clusters formed in a crowded solution may reach up to ∼700 mg/ml [26] (Figure 2B). The formation of compartments can also be regarded as phase separation, where entropic attractions in a mixture of macromolecules result in expulsion of one component as a separate phase [27].…”
Section: Macmillan Publishers Ltd 2001) (D)mentioning
confidence: 97%
“…Such crystalline-state protein is pristine without impurities or aggregates, but the crystallization itself is time-consuming and the preparation of sufficient quantities of protein is difficult. A similar mechanism has been proposed using the nanoparticle dispersion of the protein-cluster state [46]. Johnston et al, have demonstrated that 1B7 antibody in a high-concentration trehalose solution forms a kind of protein colloid with a diameter of 50-300 nm via short-range hydrophobic interactions.…”
Section: Enrichment By Precipitated Ppc For High-concentration Formulmentioning
confidence: 65%